Computer Arithmetic: Continuing a Long and Steady Emergence. - Montuschi, Paolo; Muller, Jean-Michel; de Dinechin, Florent; Vetter, Ron (Computer (00189162), 2022)
This installment of Computer's series highlighting the work published in IEEE Computer Society journals comes from IEEE Transactions on Emerging Topics in Computing.